Quantitative Assessment of Regional Dynamic Airway Collapse in Neonates via Retrospectively Respiratory‐Gated 1H Ultrashort Echo Time MRI. Issue 3 (25th September 2018) - Bates, Alister J.; Higano, Nara S.; Hysinger, Erik B.; Fleck, Robert J.; Hahn, Andrew D.; Fain, Sean B.; Kingma, Paul S.; Woods, Jason C.
Abstract : Background: Neonatal dynamic tracheal collapse (tracheomalacia, TM) is a common and serious comorbidity in infants, particularly those with chronic lung disease of prematurity (bronchopulmonary dysplasia, BPD) or congenital airway or lung‐related conditions such as congenital diaphragmatic hernia (CDH), but the underlying pathology, impact on clinical outcomes, and response to therapy are not well understood. There is a pressing clinical need for an accurate, objective, and safe assessment of neonatal TM. Purpose: To use retrospectively respiratory‐gated ultrashort echo‐time (UTE) MRI to noninvasively analyze moving tracheal anatomy for regional, quantitative evaluation of dynamic airway collapse in quiet‐breathing, nonsedated neonates. Study Type: Prospective. Population/Subjects: Twenty‐seven neonatal subjects with varying respiratory morbidities (control, BPD, CDH, abnormal polysomnogram). Field Strength/Sequence: High‐resolution 3D radial UTE MRI (0.7 mm isotropic) on 1.5T scanner sited in the neonatal intensive care unit. Assessment: Images were retrospectively respiratory‐gated using the motion‐modulated time‐course of the k ‐space center. Tracheal surfaces were generated from segmentations of end‐expiration/inspiration images and analyzed geometrically along the tracheal length to calculate percent‐change in luminal cross‐sectional area ( A % ) and ratio of minor‐to‐major diameters at end‐expiration ( r D, exp ). Geometric results were compared to clinically available bronchoscopic findings ( n  = 14). Statistical Tests: Two‐sample t ‐test. Results: Maximum A % significantly identified subjects with/without a bronchoscopic TM diagnosis (with: 46.9 ± 10.0%; without: 27.0 ± 5.8%; P < 0.001), as did minimum r D, exp (with: 0.346 ± 0.146; without: 0.671 ± 0.218; P  = 0.008). Subjects with severe BPD exhibited a far larger range of minimum r D, exp than subjects with mild/moderate BPD or controls (0.631 ± 0.222, 0.782 ± 0.075, and 0.776 ± 0.030, respectively), while minimum r D, exp was reduced in CDH subjects (0.331 ± 0.171) compared with controls ( P < 0.001). Data Conclusion: Respiratory‐gated UTE MRI can quantitatively and safely evaluate neonatal dynamic tracheal collapse, as validated with the clinical standard of bronchoscopy, without requiring invasive procedures, anesthesia, or ionizing radiation. Level of Evidence: 2 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2019;49:659–667.